Artificial Intelligence in Healthcare : A Review - Miss. Isha Anand Bhagat; Miss. Komal Gajanan Wankhede; Mr. Navoday Atul Kopawar; Prof. Dipali A. Sananse (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Artificial Intelligence (AI) is revolutionizing healthcare by enhancing diagnostic accuracy, personalizing treatments and streamlining administrative tasks through advanced algorithms and machine learning. This review examines AI’s impact across various areas, including medical imaging, diagnostics, personalized medicine, drug discovery, patient monitoring, and surgical procedures. AI’s capacity to analyze complex medical data improves clinical decision-making, predicts patient outcomes, and optimizes hospital operations. AI offers significant benefits, including reduced diagnostic errors and lower healthcare costs. The future of AI in healthcare promises further innovations, such as robotic-assisted surgery, virtual patient care via remote consultations, and advanced health monitoring with wearable devices. Embracing AI not only enhances patient outcomes but also transforms medical research and administrative efficiency, paving the way for a more accessible and effective global healthcare system. Ongoing research and regulatory oversight are essential to fully harness AI’s potential while ensuring ethical standards and patient safety.
Keywords: Artificial Intelligence; Healthcare; Health Monitoring; Disease Detection; Scope of AI